Analysis of sources of return in South African private equity - J. R. Van Niekerk; J. D. Krige (South African Journal of Business Management, 2009)
Private Equity is rapidly growing as an asset class for investors in South Africa. Local and international literature presents overwhelming evidence to suggest that Private Equity offers superior risk-adjusted returns and portfolio diversification benefits.This study addresses the question of how exactly Private Equity managers are able to achieve superior returns. A sample of 46 individual completed investments representing large buy-outs in South Africa in the period 1992 to 2007 was selected and analysed to quantitatively investigate the relationship between some of the identified sources of return and the realised internal rates of return in the case of each investment. These relationships were not found to be as strong as expected and in many cases were not supportive of the findings in the literature. Only earnings growth and an increase in the earnings multiple had a significant impact on the internal rates of return achieved according to the sample analysed.The authors conclude that investing in Private Equity is too interdisciplinary to distil the sources of return into a few concise elements. Proprietary knowledge, expertise, superior management skills, relationships and experience all seem to play a role in providing Private Equity managers with a competitive edge over their public market participants.
Keywords: 650